Constituintes de Senecio heterotrichius DC.: isolamento, elucidação estrutural, derivatização e avaliação da atividade antimicrobiana; estudo dos constituintes voláteis de outras espécies de senecio - Francescato, Leandro Nicolodi (2007)
Genus Senecio (Asteraceae) constitutes a group of cosmopolitan plants formed by more than 2000 species. Although these plants have toxicity recognized due to the presence of pyrrolizidine alkaloids, several of them are used in folk medicine. Their medicinal use can be attributed to other secondary metabolites such as flavonoids and terpenoids, being that terpenoids are compounds with recognized antimicrobial activity. In this work, the evaluation of the antimicrobial activity of the CH2Cl2 and EtOH extracts of S. heterotrichius DC., the isolation and characterization of one constituent from CH2Cl2 extract, the reaction of photooxidation of this compound in order to obtain a peroxide as well as the chemical analysis and evaluation of the antimicrobial activity of the essential oils from Senecio heterotrichius DC., S. ceratophylloides Griseb., S. oxyphyllus DC. and S. leptolobus DC. were studied. Extracts of the fresh aerial parts of S. heterotrichius were obtained by sequential maceration at room temperature in CH2Cl2 and EtOH, followed by evaporation under reduced pressure. The CH2Cl2 extract was firstly fractioned by CC over silica gel for the isolation of the sesquiterpene germacrene D and then identified by GC-MS, 1H and 13C NMR. This compound, considered a precursor of several other sesquiterpene derivatives, was submitted to photooxidation reaction using Bengal rose as sensitizer agent. The main formed peroxide was isolated from the reactional mixture by CC over silica gel, analyzed by GC-MS,1H and 13C NMR, and identified as being germacrene-D-1-hydroperoxide. The evaluation of the antimicrobial activity of the extracts of S. heterotrichius and of germacrene-D-1-hydroperoxide was accomplished through the broth microdilution method based on M27- A2/NCCLS documents for yeasts and M7-A4/NCCLS for aerobic bacteria. The extraction of the essential oils of the flowery aerial parts of Senecio heterotrichius, S. ceratophylloides, S. oxyphyllus and S. leptolobus was accomplished through hydrodestilation. The obtained essential oils were analyzed by GC-MS and their constituents were identified by the comparison of their Kovat s Indexes and their fragmentation patterns with literature data. These oils also had their antimicrobial activity evaluated following the previously mentioned methodology. The CH2Cl2 extract evidenced inhibitory activity against Candida krusei (MIC of 0.25 mg/mL) and Staphylococcus aureus (MIC of 2.5 mg/mL). The EtOH extract was inactive against the tested microorganisms. The germacrene-D-1-hydroperoxide presented inhibitory activity against S. cerevisiae (MIC of 2.5 mg/mL), and inhibited partially the growth of the algae Prototheca zoopfi at 5 and 2.5 mg/mL (inhibition of 80 and 50%, respectively). The essential oils of S. ceratophylloides and S. leptolobus exhibited inhibitory and bactericidal activity against Staphylococcus aureus and Pseudomonas aeruginosa (MIC and MBC between 6.6 and 3.3 mg/mL). The oil of S. oxyphyllus just inhibited partially the growth of these microorganisms (MIC 50% = 6.6 and 1.6 mg/mL, respectively). The oil of S. heterotrichius inhibited partially the growth of S. aureus with a MIC 50% = 3.3 mg/mL. These oils are constituted almost exclusively by mono and sesquiterpenoids, being germacrene D one of the main constituents present in all essential oils.